Application of Restorative Justice in Criminal Case Settlement in Indonesia: A Literature Perspective - Wijaya, Febry Pujiarto; Safira, Mirza Elmy; Darmawan, Didit (Bulletin of Science, Technology and Society, 2022)
This research aims to explore the application of restorative justice principles in the Indonesian criminal law system through a literature review. Restorative justice, as an alternative approach, offers a more humanist and social recovery-oriented solution compared to the traditional retributive approach. This study found that the application of restorative justice in Indonesia has been regulated through several policies, such as Law No. 11/2012 on Juvenile Justice System, but its implementation is still limited to certain cases, such as minor offenses and crimes involving children. The research also identified key challenges to implementation, including low understanding by law enforcement officials, cultural resistance to dialogic conflict resolution, and a lack of comprehensively integrated regulations. Suggestions include increased training for law enforcement officials, regulatory reform to expand the scope of restorative justice, and strengthening community participation in the legal process. This study contributes to the development of a more inclusive and equitable criminal justice system in Indonesia.